The ABCG2 rs2231142 polymorphism and the risk of nephrolithiasis: A case–control study from the Taiwan biobank - Lin, Ching-Tsai; Chen, I-Chieh; Chen, Yen-Ju; Lin, Ying-Cheng; Chang, Jui-Chun; Wang, Tsai-Jung; Huang, Wen-Nan; Chen, Yi-Hsing; Chen, Yi-Huei; Lin, Ching-Heng; Chen, Yi-Ming (Frontiers in Endocrinology, 2023)
Background: Hyperuricemia and gout are risk factors of nephrolithiasis. However, it is unclear whether the ABCG2 gene contributes to the development of nephrolithiasis. We aimed to investigate the interaction between the ABCG2 rs2231142 variant and incident nephrolithiasis in the Taiwanese population. Methods: A total of 120,267 adults aged 30–70 years were enrolled from the Taiwan Biobank data-base in this retrospective case–control study and genotyped for rs2231142. The primary outcome was the prevalence of self-reported nephrolithiasis. The odds ratio (OR) of incident nephrolithiasis was analyzed by multivariable logistic regression models with adjustment for multifactorial confounding factors. Associations of the ABCG2 rs2231142 variant with serum uric acid levels, and the incident nephrolithiasis were explored. Results: The frequency of rs2231142 T allele was 53%, and 8,410 participants had nephrolithiasis. The multivariable-adjusted OR (95% confidence interval) of nephrolithiasis was 1.18 (1.09–1.28) and 1.12 (1.06–1.18) for TT and GT genotypes, respectively, compared with the GG genotype (p<0.001), specifically in the male population with hyperuricemia. Higher age, male sex, hyperlipidemia, hypertension, diabetes mellitus, hyperuricemia, smoking and overweight were independent risk factors for nephrolithiasis. In contrast, regular physical exercise is a protective factor against nephrolithiasis. Conclusions: ABCG2 genetic variation is a significant risk of nephrolithiasis, independent of serum uric acid levels. For rs2231142 T allele carriers, our result provides evidence for precision healthcare to tackle hyperuricemia, comorbidities, smoking, and overweight, and recommend regular physical exercise for the prevention of nephrolithiasis.